(untitled) (Tamaddun, 2024)
This study investigates the language styles employed by lecturers at the State Tourism Polytechnic of Makassar during classroom interactions, focusing on their implications for the teaching and learning process. Using a qualitative research design grounded in classroom discourse analysis, the study employs a postpositivist approach to explore the nuanced communication dynamics between lecturers and students. Data were collected through observations, document reviews, and audio-visual recordings and analyzed using the Interactive Model of Data Analysis by Miles, Huberman, and Saldana. The findings reveal the absence of the frozen style, typically associated with ceremonial contexts, in classroom settings. Instead, four language styles were identified: formal, consultative, casual, and intimate. The formal style was the most prevalent, used by five lecturers to maintain structure and professionalism. The consultative style, observed in four lecturers, fostered dialogue and collaboration, while the casual style, used by three lecturers, facilitated a relaxed and approachable classroom atmosphere. The intimate style, employed by one lecturer, highlighted its role in building personal connections and providing individualized support. These findings underscore the critical role of language styles in shaping classroom interactions and enhancing student engagement. The study emphasizes the importance of linguistic adaptability and cultural sensitivity in teaching, providing practical implications for teacher training and pedagogical practices. By strategically employing diverse language styles, educators can create dynamic, inclusive, and effective learning environments. Future research should explore student perspectives and cross-cultural variations in language styles to broaden the understanding of their impact on education.